A Novel and Robust Method for Investigating Fungal Biofilm - Biswambhar Biswas; Shumaiza Asif; Rekha Puria; Anil Thakur (Bio-Protocol)
Candida auris, labeled an urgent threat by the CDC, shows significant resilience to treatments and disinfectants via biofilm formation, complicating treatment/disease management. The inconsistencies in biofilm architecture observed across studies hinder the understanding of its role in pathogenesis. Our novel in vitro technique cultivates C. auris biofilms on gelatin-coated coverslips, reliably producing multilayer biofilms with extracellular polymeric substances (EPS). This method, applicable to other Candida species like C. glabrata and C. albicans, is cost-effective and mimics the niche of biofilm formation. It is suitable for high-throughput drug screening and repurposing efforts, aiding in the development of new therapeutics. Our technique represents a significant advancement in Candida biofilm research, addressing the need for consistent, reproducible biofilm models. We detail a step-by-step procedure for creating a substratum for biofilm growth and measuring biofilm thickness using confocal laser scanning microscopy (CLSM) and ultrastructure by scanning electron microscopy (SEM). This method provides consistent outcomes across various Candida species.